2016
DOI: 10.1090/tran/6584
|View full text |Cite
|
Sign up to set email alerts
|

Affine permutations and rational slope parking functions

Abstract: We introduce a new approach to the enumeration of rational slope parking functions with respect to the area and a generalized dinv statistics, and relate the combinatorics of parking functions to that of affine permutations. We relate our construction to two previously known combinatorial constructions: Haglund's bijection ζ exchanging the pairs of statistics (area, dinv) and (bounce, area) on Dyck paths, and the Pak-Stanley labeling of the regions of k-Shi hyperplane arrangements by k-parking functions. Essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 39 publications
(112 reference statements)
0
73
0
Order By: Relevance
“…For type A n−1 we have ρ,θ = n − 1, and therefore C = {μ ∈ P + : μ,θ l − n} is the (l − n)-dilated fundamental 1-alcove C 1 = {μ ∈ P + : μ,θ 1}. Then by a result in [16], the number of the root weights in C is equal to the number of the increasing (l − n)/n parking functions, and this number is known to be given by the rational Catalan number c l−n, n [16].…”
Section: Conjectures and Commentsmentioning
confidence: 96%
“…For type A n−1 we have ρ,θ = n − 1, and therefore C = {μ ∈ P + : μ,θ l − n} is the (l − n)-dilated fundamental 1-alcove C 1 = {μ ∈ P + : μ,θ 1}. Then by a result in [16], the number of the root weights in C is equal to the number of the increasing (l − n)/n parking functions, and this number is known to be given by the rational Catalan number c l−n, n [16].…”
Section: Conjectures and Commentsmentioning
confidence: 96%
“…The reverse reading permutation of P , denoted τ (P ), encodes the relative order of the values in M (P ). In our running example, the one-line notation for σ(P ) and τ (P ) are σ(P ) = [1,3,7,12,9,13,11,8,5,10,6,4,2] and τ (P ) = [1,2,4,6,10,5,8,11,13,9,12,7,3].…”
Section: Dictionary Of Notationmentioning
confidence: 99%
“…A given label in S(π) is called an N label if the vertex associated to it is the start of an N step, otherwise it is called an E label. For example, if π is the path on the left in Figure 23 This problem has been studied by Gorsky, Mazin, and Vazirani [GMV14] and Armstrong, Loehr, and Warrington [ALW14]. See also [AHJ14].…”
Section: Tesler Matrices and The Superpolynomialmentioning
confidence: 99%
“…See also [AHJ14]. In [GMV14] it is shown that the sweep map is a bijection whenever m = kn + 1 or m = kn − 1 for some positive integer k. We note that in the case m = kn + 1 Loehr [Loe03], [Loe05b] (see also [Hag08][pp. 108-109]) has defined an extension of the bounce statistic, which when combined with area generates the q, t-Catalan for m = kn + 1.…”
Section: Tesler Matrices and The Superpolynomialmentioning
confidence: 99%